Selective recovery of vanadium as AMV from calcium vanadate sludge by direct AS leaching process: An industrial approach. (1st February 2020) - Muthukumar, K.; Patel, K.M.; Mohapatra, D.; Padh, Bharat; Reddy, B.Ramachandra
Highlights: Strategy for processing of calcium vanadate sludge to recover pure V compound. Single step process to recover AMV from calcium vanadate sludge demonstrated. Valuable metal recovery philosophy for V leached residue proposed. Proposed process overcome drawbacks of existing sulphuric acid leach process. Abstract: Generation of calcium vanadate waste sludge their management and treatment.is one of the major problem of metal processing industry. In this paper, we have proposed a simple process for the selective recovery of vanadium as ammonium metavanadate (AMV) from the calcium vanadate sludge using ammonium sulphate (AS) as a leaching agent. Under the optimum leaching condition (pH-7.5, temperature-80 °C, time-1 h, AS reagent-0.5 M) it is possible to leach out 82% of V values from the calcium vanadate sludge. The overall recovery of V is 81% with 98.5% AMV product purity. The AMV product quality from AS leach process has been compared with conventional H2 SO4 leach process. The proposed process has major advantages such as, better economic benefits, less chemical consumption, minimum effluent recycling and less waste generation.